Disparitas Harga Pangan Strategis Sebelum dan Saat Pandemi COVID-19 - Firdaus, Muhammad (Jurnal Ikatan Sarjana Ekonomi Indonesia, 2021)
This study aims to compare the variability and convergence of strategic food prices before and during the COVID-19 pandemic in Indonesia. The weekly prices data of 9 food commodities in 34 provinces during 2019 and 2020 was used. The price variability and convergence are analyzed using the coefficient of variation and dynamic data panel, respectively. The result showed that the rice, beef, red chilies, chicken meat, and chicken eggs experienced a decrease in price variability while sugar, shallots, garlic, and cayenne pepper exhibited the opposite. Prices movement among regions tends to show increasing price variability, with the exception of chicken eggs. Some efforts such as supply management through structuring production over time, efficiency of distribution between regions is imperative to stabilize food prices. Besides, efforts such as a market contract system, warehouse receipt systems and strengthening Local Government-Owned Enterprise for food supply management are crucial.Keywords: horticulture; convergence; dynamic panel data; variability AbstrakPenelitian ini bertujuan untuk membandingkan variabilitas dan konvergensi harga pangan strategis sebelum dan selama pandemi COVID-19 di Indonesia. Data yang digunakan adalah harga mingguan 9 komoditas pangan di 34 provinsi selama 2019 dan 2020. Variabilitas dan konvergensi harga dianalisis menggunakan koefisien variasi dan data panel dinamis. Hasil penelitian menunjukkan bahwa beras, daging sapi, cabai merah, daging ayam, dan telur ayam mengalami penurunan variabilitas harga, sedangkan gula, bawang merah,bawang putih, dan cabai rawit mengalami sebaliknya. Pergerakan harga antar wilayah menunjukkan variabilitas harga yang cenderung meningkat, kecuali harga telur ayam. Beberapa hal yang dapat dilakukan untuk menstabilkan harga pangan adalah manajemen pasokan melalui penataan produksi antar waktu dan efisiensi distribusi antar daerah. Selain itu, sistem kontrak pemasaran, sistem resi gudang, dan penguatan Badan Usaha Milik Daerah untuk pengelolaan pasokan makanan sangatlah penting.